2017
DOI: 10.1111/andr.12392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone administration (and its 5‐alpha‐reduction) on parenchymal organ volumes in healthy young men: findings from a dose‐response trial

Abstract: Context Animal data shows that testosterone administration increases the volume of some parenchymal organs. However, the effects of exogenous testosterone on solid abdominal organs in humans remain unknown. Objective To evaluate the effects of testosterone administration on the volume of liver, spleen and kidneys in a dose-response trial. Participants Young healthy men aged 18 to 50 years participating in the 5α-Reductase (5aR) Trial. Interventions All participants received monthly injections of 7.5 mg l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…AAS, likewise testosterone, may cause dose-related increase in the hepatic volume. It complies with the research performed on the animals and the fact that male liver is statistically larger than a female one [23].…”
Section: Types Of Liver Injury Anabolic Steroids and Hepatic Volumesupporting
confidence: 85%
“…AAS, likewise testosterone, may cause dose-related increase in the hepatic volume. It complies with the research performed on the animals and the fact that male liver is statistically larger than a female one [23].…”
Section: Types Of Liver Injury Anabolic Steroids and Hepatic Volumesupporting
confidence: 85%
“…The first evidence that this involved a testosterone-dependent signaling pathway was the observation that excess androgen administration qualitatively increased rat proximal tubule size (57). Further evidence in adult males suggests that there is a dosedependent increase in kidney volume, with an estimated 4.04-cm 3 increase per 100 mg of weekly testosterone supplementation (58). We have recently shown that male mice have greater kidney and proximal tubule size than do female mice (20,22) and that these differences were testosterone dependent (22).…”
Section: Discussionmentioning
confidence: 99%
“…A direct effect of testosterone on renal volume has been demonstrated in mouse models of young castrated males secondarily exposed to testosterone or vehicle [ 96 ]. The trophic effect of testosterone on organ development, including the kidney, has also been demonstrated in human clinical studies [ 97 ]. Thus, sexual dimorphism in renal organogenesis as early as the third trimester in the human species could be related to testosterone secretion by male fetuses in utero [ 98 ].…”
Section: Gender Differences In Kidney Development and Organogenesismentioning
confidence: 99%